space of education - Константин Лидин (Проект Байкал)
Among the metaphorical meanings of the word ‘space’, the educational space is not the least. We are completing the publication of materials about the most interesting experiment of MARCHI on designing the virtual city of Nikolograd, and we are also presenting a new building of the RANEPA in Barnaul that embodies the modern image of elite higher education.